T Lymphocytes and Inflammatory Mediators in the Interplay between Brain and Blood in Alzheimer’s Disease: Potential Pools of New Biomarkers - Anna Mietelska-Porowska; Urszula Wojda (Journal of Immunology Research)
Alzheimer’s disease (AD) is a chronic neurodegenerative disorder and the main cause of dementia. The disease is among the leading medical concerns of the modern world, because only symptomatic therapies are available, and no reliable, easily accessible biomarkers exist for AD detection and monitoring. Therefore extensive research is conducted to elucidate the mechanisms of AD pathogenesis, which seems to be heterogeneous and multifactorial. Recently much attention has been given to the neuroinflammation and activation of glial cells in the AD brain. Reports also highlighted the proinflammatory role of T lymphocytes infiltrating the AD brain. However, in AD molecular and cellular alterations involving T cells and immune mediators occur not only in the brain, but also in the blood and the cerebrospinal fluid (CSF). Here we review alterations concerning T lymphocytes and related immune mediators in the AD brain, CSF, and blood and the mechanisms by which peripheral T cells cross the blood brain barrier and the blood-CSF barrier. This knowledge is relevant for better AD therapies and for identification of novel biomarkers for improved AD diagnostics in the blood and the CSF. The data will be reviewed with the special emphasis on possibilities for development of AD biomarkers.